Measuring Instruments In Cardiology Adapted Into Portuguese Language Of Brazil: A Systematic Review - Marilia Estevam Cornélio; Neusa Maria Costa Alexandre; Thaís Moreira São-João (SciELO, 2014)
This was a systematic review aimed at identifying and characterizing measuring instruments, developed in the context of cardiology, which were adapted into Portuguese language of Brazil. Systematic searches were performed in six databases. Information extracted included cultural adaptation process and measurement properties. To assess the methodological quality of studies, criteria based on international guidelines for cultural adaptation of instruments were used. Among the 114 articles found, 14 were eligible for review. Of these, most evaluated quality of life (35.7%) and health knowledge/learning (28.6%). Most studies followed all stages of the adaptation process recommended in the literature. With respect to measurement properties, internal consistency, verified by Cronbach's alpha, was the property reported in the majority of the studies, as well as construct and criterion validity. This study is expected to provide to the scientific community a critical evaluation of adapted questionnaires available in the context of cardiology.